Building resilience beyond the COVID-19 pandemic: can it work through creative play with digital puzzles? - Damayanti, Ranie; Syarif Sumantri, Mohamad; Nurani, Yuliani (Frontiers in Education, 2024)
The COVID-19 pandemic worldwide has significant repercussions for early childhood education. In this article, we begin by discussing the impact of a world health pandemic on education and the challenges of conducting a literature review following said the COVID-19 pandemic. Specifically, we examine the challenges of literature review on building resilience in young children in the digital era. The four sections categorize the resilience literature into themes: (1) defining resilience in young children, (2) powerful play for resilience in young children beyond the COVID-19 pandemic, (3) creative play building resilience in young children, and (4) digital puzzles for resilience: case on early childhood classroom in Indonesia. Each of the four themes is presented with a narrative whose content is current, followed by a literary consensus. The article ends with changes to build resilience in young children using creative play through digital puzzles. Digital puzzles as media for creative play support young children in developing skills that will make them happier and more resilient in overcoming daily hardships. Young children can become individuals who successfully face daily hardships creatively to reconstruct themselves after experiencing bad conditions due to the COVID-19 pandemic.